HLA sharing and maternal HLA expression in couples with recurrent pregnancy loss in Taiwan - Tsun-Wen Hsiao; Ming-Ting Chung; Jen-Yu Wen; Yi-Lun Lin; Liang-Yin Lin; Yung-Chieh Tsai (Taiwanese Journal of Obstetrics & Gynecology, 2022)
Objective: The aim of this study is to investigate the frequency and distribution of human HLA sharing and maternal HLA allele expression in couples with recurrent pregnancy loss in Taiwan. Materials and methods: We retrospectively reviewed couples experienced two or more pregnancy loss before 20th weeks of gestation from March 2014 to November 2020 having HLA determination. Fertile individuals with one or more live-birth offspring receiving HLA allele determination during the same period were included as the control group. The distribution and frequency of HLA sharing were analyzed and presented by descriptive statistics. Fisher Exact Test were used to analyze specific maternal and paternal HLA allele comparing individuals with RPL to fertile group. P-value < 0.05 was thought to be statistically significant. Results: 72 couples were enrolled from March 2014 to November 2020. Regarding the distribution of HLA sharing, HLA sharing between females and their male partners less and equal to 2 pairs were found in 40.3% of the couples. HLA sharing greater and equal to 3 pairs are found in 59.8% couples. HLA sharing was most frequently found in alleles HLA-A02, A11, DQ07, C07 and B60 in descending order. There was a significant lower expression of HLA-B13 in women with RPL compared to women who had successful pregnancy (p = 0.0234). Compared infertile men with fertile men cohort, the frequency of HLA-DR04 (p = 0.0438, OR 2.444, 95% CI 1.0251–5.8287), HLA-DR12 (p = 0.001, OR 30.85, 95% CI 4.0296–236.19) and HLA-15 (p = 0.0357, OR 9.354, 95% CI 1.1610–75.37) were found to be significantly higher in men with RPL. On the contrary, HLA-DR07 (p = 0.0085, OR 0.124, 95% CI 0.0264–0.587) and HLA-DR10 (p = 0.0395, OR 0.048, 95% CI 0.0027–0.8641) were found to be significantly lower in men with RPL. Conclusion: We found a tendency to recurrent pregnancy loss in couples with more than 2 pairs of HLA sharing. The similarity of HLA sharing, the expression of maternal HLA-B13 allele and paternal HLA-DR alleles in Taiwanese couples might play a role in recurrent pregnancy loss.